DEMAND FOR HUMAN RESOURCE POTENTIAL AS A BASIS FOR INNOVATIVE DEVELOPMENT OF ECONOMY - Elena A. Okunkova (Вестник Российского экономического университета имени Г. В. Плеханова)
The article discusses questions concerning formation of human resources potential for development of innovative economy in Russia, the concept of "human resources potential", its structure and composition are revealed, the special role of the national education system and human resources in the process of the country's transition to the innovative development path is emphasized. Based on the system analysis of the problems of ensuring the demand for human resources, the author proposes introduction of regular forecasting of the demand for personnel at the regional level and formation of a targeted request to the education system as a tool to eliminate the discrepancy between the qualitative and quantitative characteristics of the human resources potential in the labor market situation.